Shoulda, Coulda, Woulda – Non-Canonical Forms on the Move? - Freudinger, Markus (Zeitschrift für Anglistik und Amerikanistik)
Abstract In this paper, the contractions shoulda, coulda, woulda are compared with their respective full forms should have , would have , and could have . Although the full forms are used much more frequently and are, therefore, considered canonical, the non-canonical forms have increased in frequency throughout the better part of the twentieth century. They are predominantly used in American English – in conversation as well as in fictional writing to imitate speech. With respect to their syntactic environment, shoulda, coulda , and woulda behave differently than their full counterparts since they are often used without subjects and without lexical verbs. Some of these uses can be explained by the fact that shoulda, coulda , and woulda are not always used as verbal items but also as nouns, adjectives, and interjections. Due to their overall low frequency and their restriction to a particular register, however, it appears they will keep their non-canonical status for the foreseeable future.
Keywords: Literature and Literary Theory; Linguistics and Language; Language and Linguistics

On the Kinda Peripheral Character of Gotta and what we Oughta Do about it - Freudinger, Markus (Exploring the Periphery)

Wie verhalten sich Aktionäre bei Unternehmenszusammenschlüssen? Modellierung sprachlicher Muster zur Analyse treibender Faktoren bei der Berichterstattung - Stotz, Sophia; Geierhos, Michaela (DHd 2016: Modellierung - Vernetzung - Visualisierung. Die Digital Humanities als fächerübergreifendes Forschungsparadigma. Konferenzabstracts, Universität Leipzig, 7. bis 12. März 2016)
Welche Informationen über Unternehmenszusammenschlüsse werden in Zeitungsnachrichten vermittelt, und wie können diese Informationen automatisch extrahiert werden? Dies soll am Beispiel des Verhaltens von Aktionären während eines Zusammenschlusses ermittelt werden. Dazu werden die wichtigsten Aussagen über das Votum der Aktionäre im Hinblick auf eine automatische Erkennung sprachlich analysiert. Im Fokus stehen dabei die Berichte über Aktionärsabstimmungen hinsichtlich der Annahme bzw. Ablehnung eines Übernahmeangebots.

Webmonitoring - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Webmonitoring

Sentimentanalyse - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Sentimentanalyse

Text Mining - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Text Mining

Crawler (fokussiert / nicht fokussiert) - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Crawler

On- and Off-Topic Classification and Semantic Annotation of User-Generated Software Requirements - Dollmann, Markus; Geierhos, Michaela (Proceedings of the 2016 Conference on Empirical Methods in Natural Language Processing (EMNLP))
Users prefer natural language software requirements because of their usability and accessibility. When they describe their wishes for software development, they often provide off-topic information. We therefore present an automated approach for identifying and semantically annotating the on-topic parts of the given descriptions. It is designed to support requirement engineers in the requirement elicitation process on detecting and analyzing requirements in user-generated content. Since no lexical resources with domain-specific information about requirements are available, we created a corpus of requirements written in controlled language by instructed users and uncontrolled language by uninstructed users. We annotated these requirements regarding predicate-argument structures, conditions, priorities, motivations and semantic roles and used this information to train classifiers for information extraction purposes. The approach achieves an accuracy of 92% for the on- and off-topic classification task and an F1-measure of 72% for the semantic annotation.

40 issues of ICAME News/ICAME Journal - Mindt, Ilka (ICAME Journal 40)

An interview with Joybrato Mukherjee, the Chair oft he ICAME Board - Kytö, Merja; Stenström, Anna-Brita; Mindt, Ilka (ICAME Journal 40)

The diachronic development of 'COME TO V' - Mindt, Ilka (Silesian Studies in English 2015)

How to Complete Customer Requirements: Using Concept Expansion for Requirement Refinement - Geierhos, Michaela; Bäumer, Frederik Simon (Proceedings of the 21st International Conference on Applications of Natural Language to Information Systems (NLDB))
One purpose of requirement refinement is that higher-level requirements have to be translated to something usable by developers. Since customer requirements are often written in natural language by end users, they lack precision, completeness and consistency. Although user stories are often used in the requirement elicitation process in order to describe the possibilities how to interact with the software, there is always something unspoken. Here, we present techniques how to automatically refine vague software descriptions. Thus, we can bridge the gap by first revising natural language utterances from higher-level to more detailed customer requirements, before functionality matters. We therefore focus on the resolution of semantically incomplete user-generated sentences (i.e. non-instantiated arguments of predicates) and provide ontology-based gap-filling suggestions how to complete unverbalized information in the user’s demand.
Keywords: Requirement refinement; Concept expansion; Ontology-based instantiation of predicate-argument structure

Evaluating bilingual education in Germany: CLIL students’ general English proficiency, EFL self-concept and interest - Rumlich, Dominik
Reviews/Rezensionen: Lasagabaster (2017) in der Zeitschrift Journal of Immersion and Content-Based Language Education, 5(1) :https://www.jbe-platform.com/content/journals/10.1075/jicb.5.1.06las] Burmeister (2019) in der Zeitschrift Fremdsprachen Lehren und Lernen, 48(1): http://www.periodicals.narr.de/index.php/flul/article/view/4836 Breeze (2018) in der Zeitschrift Estudios sobre Educación, 34(1): https://www.unav.edu/publicaciones/revistas/index.php/estudios-sobre-educacion/article/download/21762/17478

Anglistentag 2015 Paderborn: Proceedings

Religion im zeitgenössischen britischen Drama - Tönnies, Merle (Religion und Kultur)

The Use of Comic Effects in Memoirs of British Asian Adolescence: Twenty-First Century Writers Looking Back at the 1970s and 1980s - Tönnies, Merle (Anglistik. International Journal of English Studies)

The Duality of Page and Stage: Constructing Lyrical Voices in Contemporary British Poetry Written for Performance - Tönnies, Merle; Brüning, Joana; Sand, Andrea (Zeitschrift für Anglistik und Amerikanistik)

Memory, Dementia and Narrative Identity in Alice Munro’s ‘The Bear Came Over the Mountain’ - Strauß, Sara (Traces of Aging: Old Age and Memory in Contemporary Narrative)

The Making of English Popular Culture. ed. by John Storey - Flotmann-Scholz, Christina (Journal for the Study of British Cultures)

Die literarische Kommunikationsspirale: Strukturelle Wechselwirkungen zwischen literarischem Text und Rezeption in der angelsächsischen Kinder- und Jugendliteratur des späten 20./ frühen 21. Jahrhunderts. by Uta Woiwod - Flotmann-Scholz, Christina (Anglistik: International Journal of English Studies)

Oedipal Murders and Nostalgic Ressurections: The Victorians in Historical Middlebrow Fiction, 1914-1959. by Caterina Maria Grasl - Flotmann-Scholz, Christina (Literaturwissenschaftliches Jahrbuch)

Running out of Words: How Similar User Stories Can Help to Elaborate Individual Natural Language Requirement Descriptions - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 22nd International Conference on Information and Software Technologies (ICIST))
While requirements focus on how the user interacts with the system, user stories concentrate on the purpose of software features. But in practice, functional requirements are also described in user stories. For this reason, requirements clarification is needed, especially when they are written in natural language and do not stick to any templates (e.g., "as an X, I want Y so that Z ..."). However, there is a lot of implicit knowledge that is not expressed in words. As a result, natural language requirements descriptions may suffer from incompleteness. Existing approaches try to formalize natural language or focus only on entirely missing and not on deficient requirements. In this paper, we therefore present an approach to detect knowledge gaps in user-generated software requirements for interactive requirement clarification: We provide tailored suggestions to the users in order to get more precise descriptions. For this purpose, we identify not fully instantiated predicate argument structures in requirements written in natural language and use context information to realize what was meant by the user.
Keywords: Natural language requirements clarification; Syntactically incomplete requirements; Compensatory user stories

Performing Selves and Audience Design: Interview Narratives on the Internet - Mildorf, Jarmila (Narrative Theory, Literature, and New Media: Narrative Minds and Virtual Worlds)

Pragmatic Implications of ‘You’-Narration for Postcolonial Fiction: Mohsin Hamid’s "How to Get Filthy Rich in Rising Asia" - Mildorf, Jarmila (Pragmatic Perspectives on Postcolonial Discourse: Linguistics and Literature)

Audionarratology: Prolegomena to a Research Paradigm Exploring Sound and Narrative.” - Mildorf, Jarmila; Kinzel, Till (Audionarratology: Interfaces of Sound and Narrative)

Pictures into Sound: Aural World-Making in Art Gallery Audio Guides - Mildorf, Jarmila (Audionarratology: Interfaces of Sound and Narrative)

Constructing Dialogues, (Re)constructing the Past: ‘Remembered’ Conversations in Frank McCourt’s "Angela’s Ashes" - Mildorf, Jarmila (International Journal of Literary Linguistics)

Reconsidering Second-Person Narration and Involvement - Mildorf, Jarmila (Language and Literature)

Audionarratology: Interfaces of Sound and Narrative

Multisensory Imaginings: An Audionarratological Analysis of Philip Roth’s Novel Indignation and its German Radio Play Adaptation Empörung - Mildorf, Jarmila; Kinzel, Till (CounterText)

Middlebrow and Gender: 1890-1945

Filtering Reviews by Random Individual Error - Geierhos, Michaela; Bäumer, Frederik Simon; Schulze, Sabine; Stuß, Valentina (Proceedings of the 28th International Conference on Industrial, Engineering and Other Applications of Applied Intelligent Systems (IEA/AIE 2015))
Opinion mining from physician rating websites depends on the quality of the extracted information. Sometimes reviews are user-error prone and the assigned stars or grades contradict the associated content. We therefore aim at detecting random individual error within reviews. Such errors comprise the disagreement in polarity of review texts and the respective ratings. The challenges that thereby arise are (1) the content and sentiment analysis of the review texts and (2) the removal of the random individual errors contained therein. To solve these tasks, we assign polarities to automatically recognized opinion phrases in reviews and then check for divergence in rating and text polarity. The novelty of our approach is that we improve user-generated data quality by excluding error-prone reviews on German physician websites from average ratings.

Identifikation kognitiver Effekte in Online-Bewertungen - Stuß, Valentina; Geierhos, Michaela (DHd 2015: Book of Abstracts)

Erfahrungsberichte aus zweiter Hand: Erkenntnisse über die Autorschaft von Arztbewertungen in Online-Portalen - Geierhos, Michaela; Bäumer, Frederik Simon (DHd 2015: Book of Abstracts)

Der zufriedene Patient 2.0: Analyse anonymer Arztbewertungen zur Generierung eines Patientenstimmungsbildes - Geierhos, Michaela; Schulze, Sabine (ForschungsForum Paderborn)
Der Erfahrungsaustausch zwischen Patienten findet heutzutage zunehmend im Internet statt. Bewertungsportale wie jameda, DocInsider oder imedo.de bieten Patienten und deren Angehörigen die Möglichkeit, anonym Beschwerden zu äußern oder Weiterempfehlungen auszusprechen. Gleichzeitig ermöglichen diese hunderttausend Individualerfahrungen die Erhebung der Patientenzufriedenheit sowie die Überprüfung bestehender Gerüchte, wie z. B. dass Privatpatienten schneller einen Arzttermin bekommen und weniger Zeit im Wartezimmer verbringen. Die Analyse anonymer Online-Arztbewertungen kann nur dann erfolgreich sein, wenn bei der Interpretation der Patientenerfahrungsberichte berücksichtigt wird, dass behandlungsqualitätsunabhängige Faktoren Auswirkungen auf die subjektive Bewertung und das Beschwerdeverhalten haben. Ein neuer Ansatz ist daher, bedeutende Indikatoren für die Patientenzufriedenheit im Web 2.0 zur Generierung eines detaillierten Erfahrungs- und Patientenstimmungsbildes unter Berücksichtigung demographischer und regionaler Einflüsse zu ermitteln.

Interpersonal relations in biographical dictionaries. A case study - Stotz, Sophia; Stuß, Valentina; Reinert , Matthias; Schrott, Maximilian (Proceedings of the First Conference on Biographical Data in a Digital World 2015)
Adopting the concept of “Local Grammars” (M. Gross), which were successfully applied in practice by (Geierhos, 2010) to biographical information extraction in English our project aims to detect, encode, and finally visualize relations between persons. Our corpus consists of the digitised biographical lexicon “Neue Deutsche Biographie (NDB)”, roughly 21.000 biographies in 25 volumes in print since 1953. We developed local grammars and suitable dictionaries to describe interpersonal relations and applied them to the corpus with Unitex 3.1. The local grammars were designed to integrate existing TEI-XML structures in the corpus. Using the ability of local grammars in Unitex to act as transducers we were able to produce XML-Tags and encode semantic information. Based on grammars for personal names and places we described interpersonal relations like to study, predecessors and successors as well as friends and circles. Afterwards we identified persons (as given in the authority file or index). Finally we displayed relations on our website in an interactive and dynamic way. Utilizing the Javascript library D3.js we represented named relations between identified individuals as ego centred network graphs.
Keywords: Local Grammar; Relation Extraction; Visualisation

"I grade what I get but write what I think." Inconsistency Analysis in Patients' Reviews - Geierhos, Michaela; Bäumer, Frederik Simon; Schulze, Sabine; Stuß, Valentina (ECIS 2015 Completed Research Papers)
Received medical services are increasingly discussed and recommended on physician rating websites (PRWs). The reviews and ratings on these platforms are valuable sources of information for patient opinion mining. In this paper, we have tackled three issues that come along with inconsistency analysis on PRWs: (1) Natural language processing of user-generated reviews, (2) the disagreement in polarity of review text and its corresponding numerical ratings (individual inconsistency) and (3) the differences in patients’ rating behavior for the same service category (e.g. ‘treatment’) expressed by varying grades on the entire data set (collective inconsistency). Thus, the basic idea is first to identify relevant opinion phrases that describe service categories and to determine their polarity. Subsequently, the particular phrase has to be assigned to its corresponding numerical rating category before checking the (dis-)agreement of polarity values. For this purpose, several local grammars for the pattern-based analysis as well as domain-specific dictionaries for the recognition of entities, aspects and polarity were applied on 593,633 physician reviews from both German PRWs jameda.de and docinsider.de. Furthermore, our research contributes to content quality improvement of PRWs because we provide a technique to detect inconsistent reviews that could be ignored for the computation of average ratings.

Der zufriedene Patient 2.0: Analyse anonymer Arztbewertungen im Web 2.0 - Geierhos, Michaela; Schulze, Sabine; Bäumer, Frederik Simon
Der Erfahrungsaustausch zwischen Patienten findet verstärkt über Arztbewertungsportale statt. Dabei ermöglicht die Anonymität des Netzes ein weitestgehend ehrliches Beschwerdeverhalten, von dem das sensible Arzt-Patienten-Vertrauensverhältnis unbeschädigt bleibt. Im Rahmen des vorliegenden Beitrags wurden anonyme Arztbewertungen im Web 2.0 automatisiert ausgewertet, um Einflussfaktoren auf das Beschwerdeverhalten deutscher Patienten zu bestimmen und in der Gesellschaft vermeintlich etablierte „Patienten-Mythen“ aufzuklären. Die Aufdeckung von Irrtümern und Zufriedenheitsindikatoren soll längerfristig dazu dienen, Patientenäußerungen differenzierter zu interpretieren und somit zu einer nachhaltigen Verbesserung der Arzt-Patienten-Beziehung beizutragen.

Find a Physician by Matching Medical Needs described in your Own Words - Bäumer, Frederik Simon; Dollmann, Markus; Geierhos, Michaela (The 6th International Conference on Emerging Ubiquitous Systems and Pervasive Networks (EUSPN 2015) / The 5th International Conference on Current and Future Trends of Information and Communication Technologies in Healthcare (ICTH-2015) / Affiliated Workshops)
The individual search for information about physicians on Web 2.0 platforms can affect almost all aspects of our lives. People can directly access physician rating websites via web browsers or use any search engine to find physician reviews and ratings filtered by location resp. specialty. However, sometimes keyword search does not meet user needs because of the disagreement of users’ common terms queries for symptoms and the widespread medical terminology. In this paper, we present the prototype of a specialised search engine that overcomes this by indexing user-generated content (i.e., review texts) for physician discovery and provides automatic suggestions as well as an appropriate visualisation. On the one hand, we consider the available numeric physician ratings as sorting criterion for the ranking of query results. Furthermore, we extended existing ranking algorithms with respect to domain-specific types and physicians ratings on the other hand. We gathered more than 860,000 review texts and collected more than 213,000 physician records. A random test shows that about 19.7% of 5,100 different words in total are health- related and partly belong to consumer health vocabularies. Our evaluation results show that the query results fit user's particular health issues when seeking for physicians.
Keywords: Physician Discovery; Consumer Health Vocabulary; Common Terms Query

A System for Uncovering Latent Connectivity of Health Care Providers in Online Reviews - Bäumer, Frederik Simon; Geierhos, Michaela; Schulze, Sabine (Information and Software Technologies. 21st International Conference, ICIST 2015, Druskininkai, Lithuania, October 15-16, 2015. Proceedings)
The contacts a health care provider (HCP), like a physician, has to other HCPs is perceived as a quality characteristic by patients. So far, only the German physician rating website jameda.de gives information about the interconnectedness of HCPs in business networks. However, this network has to be maintained manually and is thus incomplete. We therefore developed a system for uncovering latent connectivity of HCPs in online reviews to provide users with more valuable information about their HCPs. The overall goal of this approach is to extend already existing business networks of HCPs by integrating connections that are newly discovered by our system. Our most recent evaluation results are promising: 70.8 % of the connections extracted from the reviews texts were correctly identified and in total 3,788 relations were recognized that have not been displayed in jameda.de’s network before.
Keywords: Latent Connectivity; Person Named Entity Recognition and Disambiguation; Health Care Provider Reviews

Understanding the Patient 2.0: Gaining Insight into Patients' Rating Behavior by User-generated Physician Review Mining - Geierhos, Michaela; Bäumer, Frederik Simon; Schulze, Sabine; Klotz, Caterina (Modeling and Using Context. 9th International and Interdisciplinary Conference, CONTEXT 2015, Lanarca, Cyprus, November 2-6, 2015. Proceedings)
Patients 2.0 increasingly inform themselves about the quality of medical services on physician rating websites. However, little is known about whether the reviews and ratings on these websites truly reflect the quality of services or whether the ratings on these websites are rather influenced by patients’ individual rating behavior. Therefore, we investigate more than 790,000 physician reviews on Germany’s most used physician rating website jameda.de. Our results show that patients’ ratings do not only reflect treatment quality but are also influenced by treatment quality independent factors like age and complaint behavior. Hence, we provide evidence that users should be well aware of user specific rating distortions when intending to make their physician choice based on these ratings.
Keywords: Health 2.0; Rating Behavior; Patient Opinion Mining on Physician Rating Websites

What did you mean? Facing the Challenges of User-generated Software Requirements - Geierhos, Michaela; Schulze, Sabine; Bäumer, Frederik Simon (Proceedings of the 7th International Conference on Agents and Artificial Intelligence (ICAART), Special Session on Partiality, Underspecification, and Natural Language Processing (PUaNLP 2015))
Existing approaches towards service composition demand requirements of the customers in terms of service templates, service query profiles, or partial process models. However, addressed non-expert customers may be unable to fill-in the slots of service templates as requested or to describe, for example, pre- and postconditions, or even have difficulties in formalizing their requirements. Thus, our idea is to provide non-experts with suggestions how to complete or clarify their requirement descriptions written in natural language. Two main issues have to be tackled: (1) partial or full inability (incapacity) of non-experts to specify their requirements correctly in formal and precise ways, and (2) problems in text analysis due to fuzziness in natural language. We present ideas how to face these challenges by means of requirement disambiguation and completion. Therefore, we conduct ontology-based requirement extraction and similarity retrieval based on requirement descriptions that are gathered from App marketplaces. The innovative aspect of our work is that we support users without expert knowledge in writing their requirements by simultaneously resolving ambiguity, vagueness, and underspecification in natural language.

Zur affektiv-motivationalen Entwicklung von Lernenden im bilingualen Sachfachunterricht - Rumlich, Dominik (CLIL Revisited: Eine kritische Analyse des gegenwärtigen Standes des bilingualen Sachfachunterrichts)

Selbst(bestimmt) sind die Lernenden! Ideen und Methoden für eine studierendenzentrierte Lernveranstaltung. - Rumlich, Dominik (Diversität konkret)

Jürs-Munby, K. / Carroll, J. / Giles, S. (Hg.): Postdramatic Theatre and the Political - Tönnies, Merle (Journal of Contemporary Drama in English)

Between Authenticity and Objectification: Narrating the Self in Contemporary British Drama - Tönnies, Merle (Dramatic Minds. Performance, Cognition, and the Representation of Interiority)

‘Light of Life’: Gender, Place and Knowledge in H. G. Wells’ 'Ann Veronica' - Mildorf, Jarmila (Dark Nights, Bright Lights)

Worth Pursuing? The Limits of Cognitive Narratology - Mildorf, Jarmila (Književna istorija / Literary History)

Unreliability in Patient Narratives: From Clinical Assessment to Narrative Practice - Mildorf, Jarmila (Unreliable Narration and Trustworthiness: Intermedial and Interdisciplinary Perspectives)

Towards a Local Grammar-based Persondata Generator for Wikipedia Biographies - Geierhos, Michaela (Penser le Lexique-Grammaire)
Finding information about people in the World Wide Web is one of the most common activities of Internet users. It is now impossible to manually analyze all this information and new approaches are needed that are capable of processing the large-scale heterogeneous data in order to extract the pertinent information. The Wikipedia community still puts much effort in manually adding structured data to biographical articles, the so-called Persondata template. Thanks to this kind of metadata, semantically-enriched information concerning the biographee (e.g. name, date of birth, place of birth) can be extracted and processed by search engines. But it is a rather time-consuming task and users quite often forget to add this template: some biographies contain persondata, others do not. There is considerably less work done on developing approaches to automatically enhance English Wikipedia biographies with persondata and therefore improve the quality of structured user contributions. Within this paper, we describe our method to automatically generate persondata from biographical information in Wikipedia articles.